Location of Investors and Capital Flight - Dennis P J Botman; Cees G H Diks (Tinbergen Institute, 2002)
This paper utilizes a very simple model to study the timing and determinants of speculationagainst a fixed exchange rate regime when investors are heterogeneous because of locationaldifferences. Location matters because resident players may incur smaller costs when takinga short-position, are less exposed to exchange rate risk, possess better information quality,have more knowledge about each others information sets, due to asymmetries in tax treatment,or because of the presence of government guarantees. Our model clarifies the respective rolesplayed by local and international investors during episodes of capital flight as well as theresulting room of maneuver for policymakers in emerging markets.
Keywords: 330; Locational heterogeneity; Private information; Exchange rate volatility; Illiquidity; Capital flight; Kapitalflucht; Fester Wechselkurs; Wechselkurs; Volatilität